Developing a conceptual framework of Malaysia furniture industry towards economic transformation - Osman, Nur Syazana; Abd Rahman, Khairul Aidil Azlin (2016)
The purpose of this study is to monitor the impact of government investment in the furniture industry in order to address the Malaysia economic transformation. This study uses a literature review to document the current scenarios of Malaysia furniture industry. Then, it uses data analysis and interview to identify the appropriate components of the strategic plan in enhancing the Malaysia furniture design level. Finally, it uses an expert protocol discussion to validate the benefit of the strategic plan and implements its application for Malaysia furniture design. This study develops a measurement framework for examining the landscape of Malaysia furniture industry. Besides that, this study will enhance our understanding of the furniture industry in Malaysia and strengthen the evidence base for policy developers. From this study, it meets the expectations of policy-makers, practitioners and professionals in related fields, who have been long awaiting an analytical tool to assess the status of the Malaysia furniture design industry. This study entails a methodological research to address the primary issue of building the indicators. Its intended use is audience-specific, providing a segment of readers with an analytical framework to understand the Malaysia furniture industry. This study will contribute to three sectors; firstly, the education sector will benefit in information on the development and supply of design manpower. Secondly, the industry practitioners would be informed about the current landscape of the structure of the furniture industry. Lastly, for the community stakeholders this study is provided with a yardstick to examine the status of the furniture local industry, while the policy- makers would be able to gauge its strengths and weaknesses.